Chapter 9 The Brain-Based Argument for Unconscious Sensory Qualities - Marvan, Tomas (Taylor & Francis, 2024)
This chapter explores the notion of conscious and unconscious sensory qualities and challenges the traditional view that sensory qualities are exclusively conscious. Two arguments are offered for the existence of unconscious sensory qualities: the behavioural and the neural. The upshot of both arguments is that the similarities between conscious and unconscious sensory states are much greater than typically assumed in both the philosophy of mind and the cognitive neuroscience of consciousness. In fact, both arguments (and especially the latter one, which is explored at some length in the chapter) support the view that the mechanisms of sensory qualities are literally the same in conscious and unconscious perceptual conditions. This has important implications for general theories of consciousness and for research on neural correlates of consciousness.